Investigating the link between a layer thickness and surface relief depth in an azo poly(ether imide) - Mateusz Nieborek; Dariusz Szmigiel; Paweł Komorowski; Agnieszka Siemion; Jolanta Konieczkowska; Ewa Schab-Balcerzak; Anna Kozanecka-Szmigiel (Scientific Reports)
Abstract Surface relief grating formation in photo-responsive azo polymers under irradiation is a long-ago-found phenomenon, but all the factors governing its efficiency are still not fully recognized. Here, we report on the enormous impact of the polymer thickness on the possibility of fabrication of extremely high-amplitude surface deformations. We performed prolonged holographic recordings on the layers of the same azobenzene poly(ether imide), which had substantially different optical transmittances at the recording wavelength and revealed that the depths of the inscribed relief structures increased with the polymer thickness from a nondetectable value up to almost 2 µm, unaffected by the presence of a polymer-glass substrate interface in either sample. We proposed the mathematical model for the relief buildup process under irradiation and validated the topographic data by their Fourier analysis related to optical measurements of the grating diffraction efficiencies. We believe that our study provides important guidelines when choosing the layer thickness to maximize the surface relief grating depths and contributes to a better understanding of the SRG formation mechanism.